The Role of Astrocytes in Multiple Sclerosis Progression - Correale, Jorge; Farez, Mauricio F. (Frontiers in Neurology, 2015)
Multiple sclerosis is an inflammatory disorder causing central nervous system demyelination and axonal injury. Although its etiology remains elusive, several lines of evidence support the concept that autoimmunity plays a major role in disease pathogenesis. The course ofMS is highly variable; nevertheless, the majority of patients initially present a relapsing-remitting clinical course. After 10-15 years of disease, this pattern becomes progressive in up to 50% of untreated patients, during which time clinical symptoms slowly cause constant deterioration over a period of many years. In about 15% of MS patients however, disease progression is relentless from disease onset. Published evidence supports the concept that progressive multiple sclerosis reflects a poorly understood mechanism of insidious axonal degeneration and neuronal loss. Recently, the type of microglial cell and of astrocyte activation and proliferation observed has suggested contribution of resident central nervous system cells may play a critical role in disease progression. Astrocytes could contribute to this process through several mechanisms: a) as part of the innate immune system, b) as a source of cytotoxic factors, c) inhibiting re-myelination and axonal regeneration by forming a glial scar, and d) contributing to axonal mitochondrial dysfunction. Furthermore, regulatory mechanisms mediated by astrocytes can be affected by aging. Notably, astrocytes might also limit the detrimental effects of pro-inflammatory factors, while providing support and protection for oligodendrocytes and neurons. Because of the dichotomy observed in astrocytic effects, the design of therapeutic strategies targeting astrocytes becomes a challenging endeavor. Better knowledge of molecular and functional properties of astrocytes therefore, should promote understanding of their specific role in multiple sclerosis pathophysiology, and consequently lead to development of novel and more successful therapeutic approache